Design and Analysis of Clamping Mechanism for Transmission Tower Climbing Robot - Zhao Huiru; Lu Shouyin; Shi Lirong (Jixie chuandong, 2019)
In view of the high risk and low efficiency of the manual maintenance of the safety rope during the work of the tower, the V-shaped angle steel symmetrical clamping mechanism is designed based on the principle of rhombus principle. It is mainly composed of a gripping hand, an abduction mechanism and an ejection mechanism. The clamping hand realizes the grasping of the diagonal steel by the cooperation of the screw jack and the sliding rail, and the abduction mechanism perpendicular to the clamping arm changes the position of the gripping hand by adjusting the exhibition distance thereof, and the V-shaped block on the front end of the ejector mechanism ensures that the robot body is always parallel to the angle. According to the analysis of the climbing environment of the transmission tower climbing robot, the three-dimensional model of the mechanism is drawn. The model is simplified according to the principle of rhombus principle and the rationality of the centering and the size of the mechanism is verified. The statics model is established and the clamping force is used for mechanical analysis and structural statics simulation. Through the prototype development and test, the feasibility of the clamping mechanism is preliminarily verified.